Utmost art complexity in the verse of George Herbert. - Rickey, Mary Ellen, 1929- (University of Kentucky Press, 1966)
George Herbert has always been regarded as a man of singular piety and a poet of uncommon technical ability. Until recent times, however, he was usually thought to have written prosodically ingenious but conceptually thin verse. Mary Ellen Rickey, through a close examination of Herbert's poetry, reveals the high concentration of ideas in his verse and the richness of his imagery.